Correction: Determining the factors of m-wallets adoption. A twofold SEM-ANN approach. - Imdadullah Hidayat-Ur-Rehman; Saeed Alzahrani; Mohd Ziaur Rehman; Fahim Akhter (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0262954.].